2019
DOI: 10.1017/s1930297500006094
|View full text |Cite
|
Sign up to set email alerts
|

A universal method for evaluating the quality of aggregators

Abstract: We propose a new method to facilitate comparison of aggregated forecasts based on different aggregation, elicitation and calibration methods. Aggregates are evaluated by their relative position on the cumulative distribution of the corresponding individual scores. This allows one to compare methods using different measures of quality that use different scales. We illustrate the use of the method by re-analyzing various estimates from Budescu and Du (Management Science, 2007).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
(67 reference statements)
2
10
0
Order By: Relevance
“…An important next step is to validate the utility of our findings in more practical or applied settings. One especially appealing direction would be to apply our methods on forecasting data with much longer time horizons, such as the Survey of Professional Forecasters data for economic indicators (Garcia, 2003; Han & Budescu, 2019, 2022; Himmelstein, Budescu & Han, 2022). The methods could also be validated on existing forecasting tournament data, such as from ACE or HFC, or other publicly available forecasting data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An important next step is to validate the utility of our findings in more practical or applied settings. One especially appealing direction would be to apply our methods on forecasting data with much longer time horizons, such as the Survey of Professional Forecasters data for economic indicators (Garcia, 2003; Han & Budescu, 2019, 2022; Himmelstein, Budescu & Han, 2022). The methods could also be validated on existing forecasting tournament data, such as from ACE or HFC, or other publicly available forecasting data.…”
Section: Discussionmentioning
confidence: 99%
“…Many forecasting studies rely on observational data (Han & Budescu, 2019, 2022Mandel & Barnes, 2014;Spann & Skiera, 2009), and typical forecasting tournaments allow judges to self-select the events and timing of their forecasts (Atanasov et al, 2017(Atanasov et al, , 2020Himmelstein et al, 2021;Morstatter et al, 2019). We implemented a new design where a large number of judges forecasted the same events repeatedly at the same times, eliminating many common confounds intrinsic to forecasting research, and allowing us to evaluate the forecasters at different time points.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…This function has some attractive properties: (1) it generates probabilities (and does not require any additional normalizations) for binary events, for any value of ; (2) = for three "natural" anchor points = 0, 0.5 and 1. The full LLO function and its simplified version (Equation 3) have been applied in a large body of studies and shown to enhance the accuracy of individual forecasts as well as aggregated forecasts (e.g., Atanasov et al, 2017;Budescu et al, 1997;Baron et al, 2014;Erev et al, 1994;Han & Budescu, 2019;Mellers et al, 2014;Satopää & Ungar, 2015;Shlomi & Wallsten, 2010;Turner et al, 2014). Mellers et al (2014) applied Karmarkar's transformation to data generated by more than 2,000 forecasters in a geopolitical forecasting tournament (Aggregative Contingent Estimation ACE; https://www.iarpa.gov/research-programs/ace).…”
Section: Introductionmentioning
confidence: 99%